2021
DOI: 10.1007/s00429-021-02339-z
|View full text |Cite
|
Sign up to set email alerts
|

Expression of type one cannabinoid receptor in different subpopulation of kisspeptin neurons and kisspeptin afferents to GnRH neurons in female mice

Abstract: The endocannabinoids have been shown to target the afferents of hypothalamic neurons via cannabinoid 1 receptor (CB1) and thereby to influence their excitability at various physiological and/or pathological processes. Kisspeptin (KP) neurons form afferents of multiple neuroendocrine cells and influence their activity via signaling through a variation of co-expressed classical neurotransmitters and neuropeptides. The differential potency of endocannabinoids to influence the release of classical transmitters or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…The secondary messengers inositol-1, 4, 5-trisphosphate and diacylglycerol as well as arrestin-1 and arrestin-2 contribute to hormone release [ 240 , 241 , 242 , 243 ]. While the ECS modulates the hypothalamic release of GnRH and has consequences on steroid biosynthesis in several species [ 198 ], and the expression of CB1-R has been reported in different subpopulations of kiss1 neurons in female mice [ 244 ], currently the possible correlation between the kisspeptin/GnRH system and the ECS has only been demonstrated in the hypothalamus and gonad of male amphibians [ 237 ]. Apart from the involvement in the hypothalamus the ECS also permits gametogenesis and extragonadic maturation of the male gamete [ 198 ].…”
Section: Toolkit Of Therapeutics Of Ecsmentioning
confidence: 99%
“…The secondary messengers inositol-1, 4, 5-trisphosphate and diacylglycerol as well as arrestin-1 and arrestin-2 contribute to hormone release [ 240 , 241 , 242 , 243 ]. While the ECS modulates the hypothalamic release of GnRH and has consequences on steroid biosynthesis in several species [ 198 ], and the expression of CB1-R has been reported in different subpopulations of kiss1 neurons in female mice [ 244 ], currently the possible correlation between the kisspeptin/GnRH system and the ECS has only been demonstrated in the hypothalamus and gonad of male amphibians [ 237 ]. Apart from the involvement in the hypothalamus the ECS also permits gametogenesis and extragonadic maturation of the male gamete [ 198 ].…”
Section: Toolkit Of Therapeutics Of Ecsmentioning
confidence: 99%
“…This result supported that neuronal CB1, mainly located in axon terminals of presynaptic neurons to GnRH neurons, participates in the inhibitory control of GnRH release in males. At the present, numerous studies have reported the effects of CB1 and TRPV1 signaling on GnRH modulators such as estradiol [ 53 ], kisspeptin [ 54 ], GABA [ 55 ], and ghrelin [ 56 ], among others.…”
Section: Immune Challenge On the Hypothalamic–pituitary–gonadal Axismentioning
confidence: 99%